Metode Arba’in dalam Pembelajaran Cara Cepat Membaca Kitab di Pondok Pesantren Walyathalaththaf Darussalam Petanahan - Kori Ernawati; Fikria Najitama; Maesaroh Maesaroh (IAINU Kebumen, 2023)
The objectives of this study are: To find out how the learning process uses the arba'in method and also to find out the results obtained from learning using the arba'in method. The subjects of this study were clerics, Islamic boarding schools and students. The method used in this research is the method of observation, documentation and interviews. The data analysis is collecting data, reducing data, presenting data and conclusions or levers. Based on the results of data analysis in the study of this thesis, it can be seen that the arba'in method is one of the factors that plays an important role in the success of improving the ability to read or understand the book, both the yellow book and the Koran.